Application of ICT and Job Performance of Administrative Staff in Redeemer's University, Nigeria - Adeniran, Pauline (Jewel Journal of Librarianship, 2022)
This study examines and explores the application of information communication technology by Redeemer’s University’s administrative staff and its impact on their job performances. The study employed a descriptive research design using the questionnaire instrument for data collection. The population consists of 50 administrative staff of Redeemer's University. A total enumerative sampling was adopted for the study. The data collected were analyzed using frequency, percentages, and tables. The findings revealed that most participants use ICT tools to perform their official duties. It also revealed that the respondents found it easy to use ICT tools. The findings further revealed that the use of ITC tools helped the participants to achieve quality work output. It also revealed that electricity interruption and limited ICT tools were the challenges faced by the respondents. Based on the study's findings, the researchers recommended that the Management of universities provide a constant supply of electricity. It was also recommended that government should support universities in the procurement of ICT tools to ensure the quality performance of staff duties